Analysis of dropout across the continuum of maternal health care in Tanzania: findings from a cross-sectional household survey - Mohan, Diwakar; LeFevre, Amnesty E; George, Asha; Mpembeni, Rose; Bazant, Eva; Rusibamayila, Neema; Killewo, Japhet; Winch, Peter J; Baqui, Abdullah H (Health policy and planning, 2017)
The ‘continuum of care’ is proposed as a key framework for the delivery of maternal, neonatal and child health services. This study examined the extent of dropout as well as factors associated with retention across the MNCH continuum from antenatal care (ANC), through skilled birth attendance (SBA), to postnatal care (PNC). We analyzed data from 1931 women who delivered in the preceding 2–14 months, from a twostage cluster sampling household survey in four districts of Tanzania’s Morogoro region. The survey was conducted in 2011 as a part of a baseline for an independent evaluation of a maternal health program. Using the Anderson model of health care seeking, we fitted logistic models for three transition stages in the continuum. Only 10% of women received the ‘recommended’care package (4+ANC visits, SBA, and 1+PNC visit), while 1% reported not having care at any stage. Receipt of four ANC visits was positively associated with women being older in age (age 20–34 years—OR: 1.77, 95% CI: 1.22–2.56; age 35–49 years—2.03, 1.29–3.2), and knowledge of danger signs (1.75, 1.39–2.1). A pro-rich bias was observed in facility-based deliveries (proxy for SBA), with women from the fourth (1.66, 1.12–2.47) and highest quintiles of household wealth (3.4, 2.04–5.66) and the top tertile of communities by wealth (2.9, 1.14–7.4). Higher rates of facility deliveries were also reported with antenatal complications (1.37, 1.05–1.79), and 4+ANC visits (1.55, 1.14–2.09). Returning for PNC was highest among the wealthiest communities (2.25, 1.21–4.44); catchment areas of a new PNC program (1.89, 1.03–3.45); knowledge of danger signs (1.78, 1.13–2.83); community health worker counselling (4.22, 1.97–9.05); complicated delivery (3.25, 1.84–5.73); and previous health provider counselling on family planning (2.39, 1.71–3.35). Dropout from maternal care continuum is high, especially for the poorest, in rural Tanzania. Interactions with formal health system and perceived need for future services appear to be important factors for retention. ”连续照护”是孕产妇、新生儿和儿童健康服务提供的关键框 架。MNCH 连续照护是从产前护理 （ANC） 、熟练助产护 理 （SBA） 到产后护理（PNC） 的连续过程, 本研究调查中途 退出 MNCH连续照护和继续使用的相关因素。 我们在坦桑尼亚莫罗戈罗省的四个区采用二阶段整群抽样住 户调查, 收集并分析了过去2-14个月分娩的 1931 位妇女的数 据并分析。该调查于 2011 年进行, 是一项孕产妇健康项目独 立评估基线调查的一部分。采用安德森模型分析求医行为, 建 立 Logistic 模型分析连续照护中的三个过渡阶段。 仅10%的妇女接受了推荐的整体护理 （4+ANC, SBA和1+PNC）, 1%的妇女未在任何阶段使用 MUCH 护理。接受四次 ANC 检查与年龄呈正相关（20–34 岁： OR=1.77, 95%CI 1.22–2.56； 35–49 岁： OR=2.03, 95%CI 1.29–3.2）, 与对危 险体征的了解也呈正相关 （1.75, 1.39–2.1） 。院内分娩 （SBA 的代理变量） 显示偏向富人的偏倚, 最富裕五分之一 和其次家庭的妇女院内分娩较高 （3.4, 2.04–5.66； 1.66, 1.12–2.47）, 最富裕的三分之一社区的妇女院内分娩也较高 （2.9, 1.14–7.4） 。 高院内分娩率还与产前并发症 （1.37, 1.05–1.79） 和接受4þ ANC 检查相关（1.55, 1.14–2.09） 。 与 返回医疗机构接受PNC 关联最强的是最富裕社区 （2.25, 1.21–4.44） ；新 PNC 项目服务地区 （1.89, 1.03–3.45） ； 了 解危险体征 （1.78, 1.13–2.83） ； 有社区卫生工作者咨询服务 （4.22, 1.97–9.05） ； 并发症分娩 （3.25, 1.84–5.73）； 和既 往计划生育咨询 （2.39, 1.71–3.35） 。 中途退出连续孕产妇保健的比例较高, 尤其是在坦桑尼亚贫困 人口和农村地区。与卫生体系的接触和对未来医疗服务需求 的预估可能是继续使用孕产妇保健的重要因素。 El ‘continuo de la atención’ se propone como un marco clave para la prestación de servicios de salud materna, neonatal e infantil (SMNI). Este estudio examinó el grado de deserción, así como los factores asociados con la retención a través del continuo de SMNI desde el cuidado prenatal (CPN), a través de la asistencia especializada en el parto (AEP), a la atención postnatal (APN). Analizamos los datos de 1931 mujeres que dieron a luz entre los 2 y 14 meses anteriores, de una encuesta de hogares de muestreo por grupos de dos etapas en cuatro distritos de la región de Morogoro en Tanzania. La encuesta se llevó a cabo en 2011 como parte de una línea de base para una evaluación independiente de un programa de salud materna. Usando el modelo de Anderson de la búsqueda de atención de salud, ajustamos los modelos logísticos para tres etapas de transición en el continuo. Sólo el 10% de las mujeres recibieron el paquete de atención “recomendado” (4+ visitas de CPN, AEP y 1 visita APN), mientras que el 1% informó que no había recibido atención en ninguna etapa. Haber recibido cuatro visitas de CPN se asoció positivamente con mujeres mayores en edad (edad 20-34 años—RP: 1.77, IC 95%: 1.22-2.56, edad 35 a 49 años—2.03, 1.29-3.2) y conocimiento de las señales de peligro (1.75, 1.39 – 2.1). Se observó un sesgo favorable a los ricos en los partos basados en instalaciones (lo cual representa la AEP), con las mujeres del cuarto quintil (1.66, 1.12-2.47) y el quintil más altos de la riqueza de los hogares (3.4, 2.04-5.66) y el tercio superior de las comunidades por riqueza (2.9, 1.14-7.4). También se reportaron tasas más altas de partos en instalaciones con complicaciones prenatales (1.37, 1.05-1.79), y 4+ visitas de CPN (1.55, 1.14- 2.09). El regreso a la APN fue mayor entre las comunidades más ricas (2.25, 1.21-4.44); áreas de captación de un nuevo programa de APN (1.89, 1.03-3.45); conocimiento de señales de peligro (1.78, 1.13-2.83); asesoramiento de trabajadores comunitarios de salud (4.22, 1.97-9.05); parto complicado (3.25, 1.84 – 5.73); y asesoramiento previo de proveedores de salud sobre planeación familiar (2.39, 1.71-3.35). La deserción del continuo de la atención materna es alta, especialmente para los más pobres, en las zonas rurales de Tanzania. Las interacciones con el sistema formal de la salud y la necesidad percibida de servicios futuros parecen ser factores importantes para la retención.